Respon Nelayan Terhadap Fenomena Iklim (Perspektif Sosial Ekonomi) - Wahyudi Wahyudi; Muslihin Muslihin; Mauliana Wayudi; Aisyah A Rahman; Muhammad Rizal; Rahmi Rahmi (Journal on Education, 2023)
Against the background of climate phenomena, people who rely on fishing are greatly affected by climate change. This phenomenon occurs due to global warming which causes the earth's temperature to continue to increase, thus affecting a prolonged dry season. This phenomenon is known as climate change. Alue Bi Pusong Village, which is located on the coast of Jangka District, Bireuen Regency, is a fishing community. As coastal communities, fishermen rely on the sea as a resource to supply various needs. This problem raises a study question, "How do fishing communities respond to the impacts of climate change on socio-economic life," based on these problems. This study uses a qualitative methodology. The researcher intends to provide comprehensive analysis and data through in-depth interviews and observations. This study uses the community as informant subjects by means of snowball. The results of the study have an impact that climate change causes fishermen to experience socio-economic problems. From an economic perspective, the impact of climate change has made fishing communities unable to meet their daily needs and vulnerable to poverty, while social problems, particularly the inability of fishermen to predict the season due to uncertain weather, the distance traveled to find additional fish, has reduced fishery resources.